EFEKTIVITAS BLU UPTD TRANS SEMARANG DALAM PENERAPAN CASHLESS PADA BRT TRANS SEMARANG - Irvinne Alma Dhita; Ida Hayu Dwimawanti; Tri Yuniningsih (Journal of Public Policy and Management Review, 2023)
BLU UPTD Trans Semarang has implemented non-cash or cashless payments since 2017. Since the enactment of this payment system, it is known that non-cash income that enters BLU UPTD Trans Semarang is no more than 11.05% of 100% as expected. Therefore, BLU UPTD Trans Semarang in organizing cashless payments needs to be analyzed further to assess the effectiveness of this organization. This study uses Duncan's theory to answer research problems with indicators of goal attainment, integration, and adaptation which aim to analyze the effectiveness of BLU UPTD Trans Semarang in implementing cashless at BRT Trans Semarang and to analyze factors that influence the organization, researchers use the Steers theory, namely organizational characteristics, environmental characteristics, worker characteristics and management policies and practices. In this study the research method used is descriptive qualitative. The results showed that BLU UPTD Trans Semarang in achieving goals, integration and adaptation had not fully run optimally. Factors that support BLU UPTD Trans Semarang in implementing cashless BRT Trans Semarang are organizational characteristics and management policies and practices. As for the factors that hinder BLU UPTD Trans Semarang in implementing cashless at BRT Trans Semarang are environmental characteristics and worker characteristics. The recommendations that can be given by researchers are that BLU UPTD Trans Semarang conducts socialization that is more communicative and can reach all groups and add wifi facilities to each BRT Trans Semarang fleet in order to get a more stable signal quality